Can nitrogen isotopes be used to detect the effects of burning on nitrogen cycling? A study on Pinus resinosa in Minnesota, USA - Ballantyne, Fiona (Plant Conservation Unit (PCU), 2023)
Pinus resinosa stands in Minnesota, USA were surveyed and fine and coarse roots from stands were analysed for nitrogen isotopes in an attempt to determine if fire effects nitrogen cycling. Fire increased the % nitrogen of coarse roots and changed the ratio of C: N. It may also decrease the depth of the A-horizon. It did not however affect the nitrogen isotope ratio of stands. Isotope values of coarse roots were affected by the depth of the A-horizon, which is consistent with other studies. A correlation between the 15N values of course and fine roots was found however fine roots were enriched proportionately to coarse roots. This suggests that they may be using a more enriched source of nitrogen such as ammonia although this is not conclusive. A PCA performed on site variables and isotope values determined the two major axes for sites were bum history and nitrogen cycle openness but that burning did not affect the second axis. A stepwise backwards regression showed the best predictors of a root's isotope value were, in decreasing order, the isotope value of coarse roots for fine roots and vice versa, the % nitrogen of roots and the age of stands. Coarse and fine roots showed opposite trends with % nitrogen. As the % nitrogen increased, fine roots were more 15 N enriched, again pointing to different nitrogen sources for coarse and fine roots. Older stands do appear to have a more open nitrogen cycle, as roots were 15N enriched in these stands. The availability of different forms of nitrogen may influence the 15N signal of roots especially if fine roots are preferentially using ammonia. Therefore, it is not possible to say if isotope values are due to stand openness, or due to different resources use by roots.